Internalization Of Balance And Justice Value Sharia Economic System In Indonesia - Syahruddin Yasen (Jurnal Hukum Ekonomi Syariah, 2018)
AbstractIndonesian Muslims in stages since the 1950s have made important changes in the economy that contains usury and has begun to change in the Islamic economy. The flow of capital and financial circulation which has been driven by conventional banking which is used to enrich one party and another party, is always faced with the flow of religious awareness of the Muslim community. The economic system used is a monopolistic economy that is involved materialistically and freedom of taste.The purpose of this study is to provide an understanding of the sharia economic economic phenomena and the freedom of people associated with sharia principles in economics and finance in Indonesia.By analyzing Islamic theories originating from the Qur'an and hadith and the opinions of experts, this paper aims to produce the internalization of values and balance in economic distribution. Basically, the basic values and balance in the economic system have not yet been implemented by islam, even though there are already laws on sharia banking, the law on zakat and the National Sharia Council. Efforts to literate the principles of Islamic economics have not yet tied the lowest level of society, have never been well thought out by Islamic religion.Keywords: al Adl, al Qisth, equality, justice, maximum satisfaction